Multielemental analysis in Nerium Oleander L. leaves as a way of assessing the levels of urban air pollution by heavy metals. (October 2019) - Santos, Ramon S.; Sanches, Francis A.C.R.A.; Leitão, Roberta G.; Leitão, Catarine C.G.; Oliveira, Davi F.; Anjos, Marcelino J.; Assis, Joaquim T.
Abstract: In this study, Nerium oleander L. leaves were used as biomonitors to evaluate environmental pollutants levels in a sub-region in the Metropolitan Area of Rio de Janeiro City (Brazil) through X-ray Fluorescence (XRF). Control samples were collected in a rural zone next to the Parque Estadual da Pedra Branca/RJ. The samples were collected during all seasons of 2015 (summer, fall, winter and spring). The concentration of 13 elements (S, Cl, K, Ca, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ba and Pb) was determined. Most of the elements showed, during all seasons, median concentrations of sampling sites higher than the results obtained from the control sites. The principal component analysis (PCA) showed the grouping of the elements in two main factors that can be associated to emission sources of these elements. The elements Cl, K, Ca, Cu, Rb and Sr can be associated as a possible influence from the soil (root uptake and/or resuspension). On the other hand, the elements Fe, Cu, Zn, and Pb can be associated to vehicle and industry emission sources. The study showed that the XRF technique applied to Nerium oleander L. leaves is efficient to environmental pollution analysis in Metropolitan Regions since it is precise, fast and low-cost, besides allowing the monitoring of pollution levels over time. Highlights: Analyze Nerium oleander L. leaves using X-ray Fluorescence. Environmental pollution by heavy metals. Deposition, accumulation and distribution of metal pollutants. Air pollutants can be generated by natural or anthropogenic sources.